The differential processing of telomeres in response to increased telomeric transcription and RNA-DNA hybrid accumulation - Balk, Bettina; Dees, Martina; Bender, Katharina; Luke, Brian (RNA biology, 2014)
Telomeres are protective nucleoprotein structures at the ends of eukaryotic chromosomes. Despite the heterochromatic state of telomeres they are transcribed, generating non-coding telomeric repeat-containing RNA (TERRA). Strongly induced TERRA transcription has been shown to cause telomere shortening and accelerated senescence in the absence of both telomerase and homology-directed repair (HDR). Moreover, it has recently been demonstrated that TERRA forms RNA-DNA hybrids at chromosome ends. The accumulation of RNA-DNA hybrids at telomeres also leads to rapid senescence and telomere loss in the absence of telomerase and HDR. Conversely, in the presence of HDR, telomeric RNA-DNA hybrid accumulation and increased telomere transcription promote telomere recombination, and hence, delayed senescence. Here, we demonstrate that despite these similar phenotypic outcomes, telomeres that are highly transcribed are not processed in the same manner as those that accumulate RNA-DNA hybrids.